Study on cardiac autonomic modulation with the Severity of metabolic syndrome - N. BHAGYASHREE; DR. C. RAMASWAMY; H. MANJUNATH; DR. GANESH. M (International Journal of Pharma and Bio Sciences, 2017)
Metabolic syndrome is a cluster of interconnected risk factors for cardiovascular disease which includes obesity, diabetes, hypertension and dyslipidemia. Heart rate variability is used to detect cardiac autonomic dysfunctions. Objective of the study is to compare the cardiac autonomic modulation by Time – Domain parameters of HRV with the metabolic syndrome and its severity. A total of 195 patients were divided into 3 groups as group I with those having only 3 components of the metabolic syndrome, group II with more than 3 components of the metabolic syndrome and group III with less than three components of the metabolic syndrome. The group I served as normal MS people, the group II as severe MS and group III as control group. The Time-domain HRV parameters like mean HR, mean RR, RMSSD, NN50 and pNN50 were recorded in those subjects and were analyzed by ANOVA. The result showed that group II had high mean HR values and low RMSSD values than group I and group III. Mean HR and RMSSD parameters of group II and group III were comparable. Mean RR values of group II showed less value which was comparable between group I and II and group II and III. NN50 and pNN50 values showed no significant (p = 0.08) difference across the groups. Metabolic syndrome increases the sympathetic activity and decreases the parasympathetic activity causing abnormal cardiac autonomic control and it is proportionate with severity of metabolic syndrome. HRV can be used as a screening and diagnostic tool for metabolic syndrome population.